Characterization of gas‐bearing sediments in the coastal environment using geophysical and geotechnical data. Issue 5 (22nd August 2022) - Dusart, Judith; Tarits, Pascal; Fabre, Maud; Marsset, Bruno; Jouet, Gwenaël; Ehrhold, Axel; Riboulot, Vincent; Baltzer, Agnès
Abstract: Seismic investigation in marine gas‐bearing sediments often fails to get information below the acoustic mask created by free gas. To circumvent this problem, we combined collocated multichannel ultra‐high resolution seismic imaging, marine electrical resistivity tomography and core sampling to study the physical properties of gas‐bearing sediments in the Bay of Concarneau (France). We obtained sections of compression (P‐) wave velocity ( V P V_P ) from the multichannel processing and 2D resistivity models from the marine electrical resistivity tomography data inversion. We observed low resistivity (∼0.5 Ω·m) and low V P V_P (∼1200 m/s) values where free gas was identified in the seismic data. We tested a joint processing workflow combining the 1D inversion of the marine electrical resistivity tomography data with the 2D P‐wave velocity through a structural coupling between resistivity and velocity. We obtained a series of 2D resistivity models fitting the data whilst in agreement with the V P V_P data. The resulting models showed the continuity of the geological units below the acoustic gas fronts, which are associated with paleo‐valley sediment infilling. We were able to demonstrate relationships between resistivity and velocity differing from superficial to deeper sediments. We established these relationships at the geophysical scale and then compared the results to data from core sampling ( V P V_P and porosity). We inferred the porosity distribution from the marine electrical resistivity tomography data. At the core locations, we observed a good agreement between this geophysical scale porosity and the core data both within and outside the gas‐bearing sediments. This agreement demonstrated that resistivity could be used as a proxy for porosity where no V P V_P was available below gas caps. In these regions, the observed low resistivity showed a high porosity (60%–70%) down to about 10–20 m in depth, in contrast with the surrounding medium that has a porosity of less than 55%. These results support the hypothesis that failures inside the paleo‐valley sediment could control the gas migration.